Rekonstruksi Kepastian Hukum Penguasaan dan Peralihan Tanah Perwatasan di Kota Tarakan dalam Sistem Administrasi Pertanahan - Ismail ismail (Jurnal Hukum Lex Generalis, 2026)
This study examines the legal status of tanah perwatasan in Tarakan City and formulates its integration with land administration. Using normative legal research with statutory and conceptual approaches, this study finds that tanah perwatasan is merely a local social term rather than a category of land right. Therefore, physical possession and statements acknowledged by a village head must be assessed alongside possession history, parcel boundaries, land records and third-party objections. To connect social recognition with legal certainty, this study proposes an eleven-stage, non-constitutive Gradual Integration Model. The model neither replaces land registration nor assumes ATR/BPN authority and suspends routine procedures whenever material objections or disputes arise.